The Use AI Chatbots in Speaking Learning at Tarbiyatul Banat Islamic Boarding School: Santri's Perception - Nisa, Khoirun; Kusworo, Budik (International Journal on Advanced Science, Education, and Religion, 2026)
This study investigates the perceptions of students at Tarbiyatul Banat Islamic Boarding School regarding the use of AI chatbots in English-speaking practice. Employing a descriptive-qualitative method with a phenomenological approach, data were gathered through observations, interviews, and documentation from purposively selected students experienced in AI-assisted speaking. Thematic analysis revealed that AI chatbots enhance speaking confidence, provide a comfortable and judgment-free practice environment, enrich vocabulary, and improve pronunciation through real time feedback. However, institutional restrictions on device and internet use limit consistent practice. The study concludes that AI chatbots can serve as an effective complement to traditional learning if integrated in ways that align with school policies and cultural values, such as embedding them into classroom activities, developing offline tools, or using institution-approved platforms